The trunk muscles behavior in women with low back pain in the test of flexion and extension of the trunk - Nava, Guilherme Thomaz de Aquino; Tozim, Beatriz Mendes; Morcelli, Mary Hellen; Navega, Marcelo Tavella (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
INTRODUCTION: Chronic low back pain has a direct repercussion on the activities of daily living and the alteration of motor control is its main cause. This change leads to instability of the trunk stabilizer systems that control movements. Trunk flexion and extension movements associated with external disturbances may increase the potential for motor control error, resulting in injury and pain. OBJECTIVE: To evaluate and compare the recruitment of the trunk stabilizer muscles, with and without load, in the flexion and extension movements of the trunk. METHODS: Thirty - four sedentary women were evaluated, aged between 30 and 59 years, divided into: low back pain group (LBPG n = 19) and control group (CG n = 15). The protocol consisted of clinical evaluation, pain evaluation, strength test of extensor trunk muscles and trunk flexion and extension tests (TFET). Muscle electromyography in internal oblique (IO), lumbar multifidus (LM), rectus abdominis (RA), external oblique (EO) and lumbar iliacus (LI) were performed simultaneously. Multivariate analysis of variance was used with two-way repeated measurements. RESULTS: LBPG presented a trend of greater recruitment in all muscles and loads evaluated, with muscle activation up to 47% higher when compared to CG. In the intergroup comparison, the global muscles demonstrated a tendency for greater activation in LBPG, with values up to 53% higher when compared to CG, and predominantly high effect size d> 0.80. In the intragroup comparison, the IO, EO, LI and LM muscles of the LBPG presented ascending muscle recruitment with increased load the opposite was seen in the CG, which showed increased activation only in the LI and LM muscles. CONCLUSION: Women with low back pain need more muscle recruitment to remain stable and, in challenging situations, use inefficient strategies.